2012
DOI: 10.1016/j.combustflame.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-nitrogen conversion in the combustion of small amines using dimethylamine and ethylamine as biomass-related model fuels

Abstract: Laminar premixed flames of the two smallest isomeric amines, dimethylamine and ethylamine, were investigated under one-dimensional low-pressure (40 mbar) conditions with the aim to elucidate pathways that may contribute to fuel-nitrogen conversion in the combustion of biomass. For this, identical flames of both fuels diluted with 25% Ar were 2 studied for three different stoichiometries (Φ=0.8, 1.0, and 1.3) using in situ molecular-beam mass spectrometry (MBMS). Quantitative mole fractions of reactants, produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 84 publications
2
96
0
Order By: Relevance
“…Morpholine, dimethylamine, ethylamine and pyrrolidine have been used as the model nitrogen containing biomass [173][174][175][176][177]. The fact that HCN formed from biomass was taken as evidence that nitrogen in biomass could not be in protein or amino acids, but rather in heterocyclic aromatic structures.…”
Section: Nitrogen Functionality In Biomassmentioning
confidence: 99%
“…Morpholine, dimethylamine, ethylamine and pyrrolidine have been used as the model nitrogen containing biomass [173][174][175][176][177]. The fact that HCN formed from biomass was taken as evidence that nitrogen in biomass could not be in protein or amino acids, but rather in heterocyclic aromatic structures.…”
Section: Nitrogen Functionality In Biomassmentioning
confidence: 99%
“…Votsmeier et al studied monomethylamine thermal decomposition in a shock tube, employing NH 2 concentration time‐history measurements. Recently, Lucassen et al studied the laminar premixed flames of DMA and ethylamine under one‐dimensional low‐pressure conditions . In that work, a detailed combustion model was developed to analyze the major pathways in the two flames, which successfully captured many trends observed in the flame experiments .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation and pyrolysis of EA [10,11] was found to afford nitrogen oxides (NOx), HCN, NH 3 and other nitrogenated species. By simulating ignition delay times and NH 2 concentration time-histories, it was found that the decomposition of the EA molecule proceed with an activation energy of 290 kJ/mol [10].…”
Section: Page 4 Of 33mentioning
confidence: 99%